Soluble Form Production of Recombinant Human Insulin-Like Growth Factor-1 by NusA Fusion Partner in E. coli - Hemmati, Sara; Ranjbari, Javad (Trends in Peptide and Protein Sciences, 2019)
Insulin-Like Growth Factor-1 (IGF-1) is a small peptide with 70 amino acids and 7.6 kDa molecular weight that acts as the major mediator of growth hormone. According to the previous studies, recombinant production of human IGF-1 (rhIGF-1) in E. coli has resulted in an inactive form of protein (inclusion body). There are several strategies to transform inclusion body to a soluble form. Production in the form of fusion proteins as a suitable strategy, helps researcher in recombinant production of proteins in the soluble and active form. In current study, NusA fusion protein was used to produce IGF-1 soluble form, instead of insoluble protein. In previous study, rhIGF-1 was optimally expressed in inclusion body with 1.2 g/L concentration. rhIGF1 -NusA construct was cloned and expressed in E. coli, then, cell lysate was analyze by SDS-PAGE and densitometry techniques, to assay soluble and insoluble form of rhIGF-1. Results showed that rhIGF-1 concentration in soluble phase was 0.14 g/L, indicating that about 12% of total expression of rhIGF-1 was in the soluble form through NusA-fusion protein strategy. These results confirmed that some fusion proteins like NusA could improve the solubility of recombinant proteins expressed in heterogeneous bacterial hosts. HIGHLIGHTS Fusion proteins is a suitable strategy for recombinant production of proteins in e soluble form. NusA fusion tag improves the solubility of recombinant proteins expressed in bacterial hosts. NusA fusion protein convert IGF-1 insoluble form to soluble form in E. coli.